The Role of Leadership, Communication and Commitment in Effective Organizational Change - Budiono (Journal of Economics, Business, and Government Challenges, 2024)
The impact of globalization, changes in consumer demands, new technology, and new expectations from society have made organizations face new threats and opportunities. Organizational changes need to be made so that an organization can continue to have a competitive advantage and survive. Organizations really need to be able to find the right changes and manage those changes effectively. Change models that provide an overview of the important stages in an effective organizational change process have been developed by many researchers. Organizational change can occur whether planned or unplanned. Organizations can make changes to existing products, structures, strategies or people. Whatever type of change occurs in an organization, organizational change will fail if there is no effective communication, appropriate leadership, employee commitment, and readiness to change. Organizational leaders know that change needs to be managed effectively in order to achieve desired results. There are many factors that can create effective organizational change. This research focuses on the impact of leadership, communication and employee commitment on organizational change. Organization members who will implement changes in an organization. They may resist change if they do not have adequate information about why the organization needs change and what the results of the proposed change will be. In addition, leadership has a very important role in organizational change. Organization members need to feel a sense of security from their leaders, so they feel confident that change will improve the organization and bring benefits to all of them. Organization members really need to know whether the organization has the capability to implement the proposed changes. Keywords: communication, change management, employee commitment, leadership